Water Quality Awareness and Breastfeeding: Evidence of Health Behavior Change in Bangladesh - Keskin, Pinar; Shastry, Gauri Kartini; Willis, Helen (The Review of Economics and Statistics, 2017)
Decades of campaigns have cautioned households in Bangladesh about waterborne contaminants such as arsenic. In addition to switching water sources, mothers can protect young children from contaminated water by breastfeeding longer. We exploit time series variation in whether children were born before or after a nationwide information campaign and geographic variation in exposure to arsenic. We find that mothers breast-feed children longer in response to the campaign, especially when they have less access to uncontaminated wells, and that infants are more likely to be exclusively breast-fed. We find consistent evidence of lower mortality rates and diarrheal incidence for infants.